2023
DOI: 10.1109/access.2022.3233877
|View full text |Cite
|
Sign up to set email alerts
|

Wave Propagation Modeling Techniques in Tunnel Environments: A Survey

Abstract: The prediction of radio signal transmission in tunnels is important for wireless communication link design as it enables the delivery of optimum power to the intended receiver inside the tunnel. Several techniques have been proposed to estimate path loss for wireless communication inside tunnels. The radio coverage range and where base stations need to be installed can be figured out with the help of propagation models. At the time of developing these models, modeling complexity and environmental attributes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 99 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…The WDF allows the field to be represented as a set of GO rays when diffraction is considered. It can be seen that the EM field transmission by the GO rays leads to excellent results for frequencies 10 and 100 times lower [20] (also published as GJM [21]), which are known to have significantly higher diffraction than in this study. In addition, this experimental study shows that it is possible to reduce the scale and work with a small model of the tunnels.…”
Section: Research Purposesupporting
confidence: 54%
See 1 more Smart Citation
“…The WDF allows the field to be represented as a set of GO rays when diffraction is considered. It can be seen that the EM field transmission by the GO rays leads to excellent results for frequencies 10 and 100 times lower [20] (also published as GJM [21]), which are known to have significantly higher diffraction than in this study. In addition, this experimental study shows that it is possible to reduce the scale and work with a small model of the tunnels.…”
Section: Research Purposesupporting
confidence: 54%
“…This is because the energetic distribution of the Ey beam is uneven on the aperture, consisting of four peaks. It can be concluded that the dominant mode at the resonant frequency is mode TE 21 .…”
Section: Wdf Simulationsmentioning
confidence: 99%
“…Let us mention that this concept of CMD was also applied to study the stationarity of the scatterer contributions in wideband car-to-car channels, [16]. The coefficient characterizing the distance between the two correlation matrices R(z) and R(z+dz) calculated from the H transfer matrix, is defined as : (1) where f is the Froebenius norm.…”
Section: Axial Correlation and Distance Of Stationaritymentioning
confidence: 99%
“…Wireless communications in confined areas, as in road and railway tunnels have already been widely studied and a survey examining current advancements for modeling the propagation of waves in tunnels is presented in [1]. The frequency band under consideration often extends from about 1 GHz up to mm waves but, for road tunnels, special emphasis is placed on the 5.9 GHz band which is the allocated band in Europe dedicated to intelligent transport systems (ITS).…”
Section: Introductionmentioning
confidence: 99%
“…Radio wave propagation in tunnels has been extensively studied over decades [1][2][3][4][5][6]. With the emergence of new wireless communication systems such as communication-based traincontrol (CBTC) systems and 5G/6G wireless systems [7][8][9], there has been an increasing interest in radio wave propagation studies, as the development and deployment of those emerging systems rely on the prior knowledge of the propagation characteristics in the given railway environment.…”
Section: Introductionmentioning
confidence: 99%